A study on the affects of Foreign Direct Investment (FDI), inflation, unemployment and government expenditure on the economic growth in Malaysia / Nur Aien Aluwi - Aluwi, Nur Aien (Faculty of Business and Management, 2007)
This study is undertaken to examine the affects of foreign direct investment (FDI), inflation, unemployment and government expenditure on the economic growth using time series data on Malaysia (for 31 years). The objective of this study is to identify whether those factors affectionate economic growth in Malaysia. All the data used are in annual basis range from the year 1975 until year 2005. The method used is Multiple Linear Regression Analysis in order to determine the relationship between the four variables. Thus, the major findings of this study indicate that foreign direct investment and government expenditure are two important variables associated with the economic growth in Malaysia. Meanwhile, inflation and unemployment had shown insignificant relationship with the economic growth. These findings suggest that government should take into account that those factors had given big impact in determining the economic growth in Malaysia and do take corrective actions towards achieving vision 2020.